2020
DOI: 10.1111/ene.14164
|View full text |Cite
|
Sign up to set email alerts
|

Stroke unit admission is associated with better outcome and lower mortality in patients with intracerebral hemorrhage

Abstract: Background and purpose There is no clear consensus among current guidelines on the preferred admission ward [i.e. intensive care unit (ICU) or stroke unit (SU)] for patients with intracerebral hemorrhage. Based on expert opinion, the American Heart Association and European Stroke Organization recommend treatment in neurological/neuroscience ICUs (NICUs) or SUs. The European Stroke Organization guideline states that there are no studies available directly comparing outcomes between ICUs and SUs. Methods We perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
1
13
1
1
Order By: Relevance
“…A prospective observational study of 10 811 consecutive patients with spontaneous ICH who were not comatose and did not require mechanical ventilation in the first 24 hours from admission found that treatment in a stroke unit was associated with improved functional outcomes compared with treatment in either an ICU (OR, 1.27 [95% CI, 1.09–1.46]) or a general ward and that mortality was higher in an ICU (OR, 2.11 [95% CI, 1.75–2.55]) or a general ward compared with a stroke unit. 237 In a subgroup analysis of severely affected patients (NIHSS score 10–25), adjusted mortality was not different when stroke units were compared with neurointensive care units, although the odds of a poor outcome (mRS score >3) was significantly lower for patients treated in a neurointensive care unit (OR, 0.45 [95% CI, 0.26–0.79]). Other nonrandomized prospective studies that included patients with ICH have reported reduced fatality and improved outcomes, especially at longer-term follow-up.…”
Section: Medical and Neurointensive Treatment For Ichmentioning
confidence: 96%
“…A prospective observational study of 10 811 consecutive patients with spontaneous ICH who were not comatose and did not require mechanical ventilation in the first 24 hours from admission found that treatment in a stroke unit was associated with improved functional outcomes compared with treatment in either an ICU (OR, 1.27 [95% CI, 1.09–1.46]) or a general ward and that mortality was higher in an ICU (OR, 2.11 [95% CI, 1.75–2.55]) or a general ward compared with a stroke unit. 237 In a subgroup analysis of severely affected patients (NIHSS score 10–25), adjusted mortality was not different when stroke units were compared with neurointensive care units, although the odds of a poor outcome (mRS score >3) was significantly lower for patients treated in a neurointensive care unit (OR, 0.45 [95% CI, 0.26–0.79]). Other nonrandomized prospective studies that included patients with ICH have reported reduced fatality and improved outcomes, especially at longer-term follow-up.…”
Section: Medical and Neurointensive Treatment For Ichmentioning
confidence: 96%
“…National guidelines universally recommend well-organised, interdisciplinary, acute stroke unit (ASU) care [1][2][3][4], based upon consistent evidence from systematic reviews and individual trials showing improved survival and functional recovery [5,6], with the treatment effect being consistent across a range of patient characteristics within all age groups and different stroke subtypes [7][8][9][10]. However, such care is absence or only partially established in many hospitals around world [11].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ICH treated on a specialized stroke unit have been shown to have reduced risks of death or dependency (RR ¼ 0.81, 95% CI 0.71-0.92, p < 0.0001), 39 decreased in-hospital mortality (OR ¼ 3.4; 95% CI 1.65-7.6), 40,41 and improved short and long-term survival 42 compared with care on nonspecialized units.…”
Section: Section 2: Recommendations On Acute Inpatient Care Followingmentioning
confidence: 99%
“…While it is now well-accepted that patients with ischemic stroke admitted to a stroke unit featuring dedicated beds and staff have better outcomes compared with patients admitted to general or less-specialized units, there is also evidence that the subset of patients who have experienced ICH realize the same benefits. Patients with ICH treated on a specialized stroke unit have been shown to have reduced risks of death or dependency (RR = 0.81, 95% CI 0.71–0.92, p < 0.0001), 39 decreased in-hospital mortality (OR = 3.4; 95% CI 1.65–7.6), 40,41 and improved short and long-term survival 42 compared with care on nonspecialized units.…”
Section: Recommendations On the Management Of Intracerebral Hemorrhagementioning
confidence: 99%